Common ethical dilemmas of family caregivers of palliative patients in Indonesia - Martina Sinta Kristanti; Kusmaryanto Kusmaryanto; Christantie Effendy (Belitung Raya Foundation, Indonesia, 2021)
Family caregivers, especially in Asian countries, have a profound role in caring for a sick family member. However, there are wide variations between the Asian and western world in terms of culture and facilities. Therefore, the problems and needs of family caregivers between those two regions may also be distinct, and it is important to explore and elaborate based on our empirical evidence. In Indonesia, motives and values in caregiving and religion become the wheel-power of the family caregivers in providing care. This affects action and consequences for caregivers. This paper attempts to elaborate on common ethical dilemmas that usually face by family caregivers in Indonesia. Unfortunately, family caregivers typically are not prepared to make those challenging decisions. Therefore, we recommend not only that family caregivers need to be involved in the caring process, but also their issues and ethical dilemmas should be assessed and addressed by health care professionals, especially nurses, who have the most frequent contact with patient and family caregiver.